2021
DOI: 10.1161/atvbaha.120.314156
|View full text |Cite
|
Sign up to set email alerts
|

E17241 as a Novel ABCA1 (ATP-Binding Cassette Transporter A1) Upregulator Ameliorates Atherosclerosis in Mice

Abstract: Objective: Reverse cholesterol transport, removing excess cholesterol from peripheral tissues, is an important therapeutic target for atherosclerosis treatment. In this study, we propose a new small molecule, E17241, that may be used to treat atherosclerosis by promoting reverse cholesterol transport via ABCA1 (ATP-binding cassette transporter A1) upregulation. Approach and Results: E17241 (4-(1,3-dithiolan-2-yl)-N-(3-hydroxypyridin-2-yl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…In vascular smooth muscle cells, the inhibition of myocardin regulates ABCA1 to prevent atherosclerosis [ 189 ]. Recently, E17241 (4-(1,3-dithiolan-2-yl)-N-(3-hydroxypyridin-2-yl) benzamide) was identified as a novel ABCA1 upregulator and reduced atherosclerotic lesion areas in vivo in animal models [ 190 ]. An in vitro study showed that mangiferin, an agonist of NFE2 like bZIP transcription factor 2, obviously reduced TC, TG, and LDL-c levels by augmenting the expression of ABCA1 [ 164 ].…”
Section: Abca1 and Cardiovascular Diseasesmentioning
confidence: 99%
“…In vascular smooth muscle cells, the inhibition of myocardin regulates ABCA1 to prevent atherosclerosis [ 189 ]. Recently, E17241 (4-(1,3-dithiolan-2-yl)-N-(3-hydroxypyridin-2-yl) benzamide) was identified as a novel ABCA1 upregulator and reduced atherosclerotic lesion areas in vivo in animal models [ 190 ]. An in vitro study showed that mangiferin, an agonist of NFE2 like bZIP transcription factor 2, obviously reduced TC, TG, and LDL-c levels by augmenting the expression of ABCA1 [ 164 ].…”
Section: Abca1 and Cardiovascular Diseasesmentioning
confidence: 99%
“…We need to explore the influence of single miRNA-target interaction further and develop new methods to regulate miRNA biology. In addition to noncoding RNA molecules, there are also some compounds such as E17241 and N-benzothiazolyl-2-benzenesulfonamide that promote cholesterol efflux by enhancing ABCA1 mRNA and protein expression in cells and have been identified as novel ABCA1 expression upregulators [38,39]. Some substances, including leonurine, E3317, mangiferin, Shen-Hong-Tong-Luo, and celastrol, prevent AS via the oxidative stress pathway or participate in the inflammatory response to enhance ABCA1 function by upregulating the expression of ABCA1 via the peroxisome proliferator-activated receptor gamma (PPAR-γ)/liver X receptor alpha (LXR-α)/ABCA1 pathway; this promotes cholesterol efflux and reduces lipid accumulation, thus preventing AS [40][41][42][43][44].…”
Section: Recent Progress In the Anti-as Applications Of Abca1mentioning
confidence: 99%
“…We need to explore the influence of single miRNA-target interaction further and develop new methods to regulate miRNA biology. In addition to noncoding RNA molecules, there are also some compounds such as E17241 and N -benzothiazolyl-2-benzenesulfonamide that promote cholesterol efflux by enhancing ABCA1 mRNA and protein expression in cells and have been identified as novel ABCA1 expression upregulators [ 38 , 39 ].…”
Section: Abca1mentioning
confidence: 99%
“…In this issue of Arteriosclerosis, Thrombosis, and Vascular Biology , Xu et al 18 identify the small molecule E17241 in an ABCA1 promoter luciferase reporter assay high-throughput screen in HepG2 cells. E17241 dose-dependently upregulates Abca1 mRNA expression in macrophages and hepatocytes and increases macrophage cholesterol efflux to apolipoprotein A-I in vitro and macrophage reverse cholesterol transport in vivo.…”
mentioning
confidence: 99%
“…At 2 different doses, daily gavage of E17241 showed atheroprotective effects in mice deficient in apolipoprotein E ( Apoe −/− mice) fed a Western-type diet, accompanied by increases in Abca1 protein expression in macrophages of atherosclerotic plaques and in hepatocytes. 18 Plasma levels of HDL-cholesterol were not affected, presumably because hepatic levels of the scavenger receptor BI (SR-BI) were also increased by E17241. E17241 decreased plasma ALT (alanine aminotransferase) and AST (aspartate transaminase) levels, suggesting no hepatic toxicity.…”
mentioning
confidence: 99%